La méthode des itinéraires photographiques : une ethnographie visuelle des mondes ouvriers de la logistique - Cecile Cuny; Hortense Soichet; Nathalie Mohadjer (EchoGéo, 2022)
This article presents the approach set up in the framework of a collective research programme on the "social worlds of logistics blue collars", carried out on four French and German sites between 2016 and 2019. One of the aim was to turn fieldwork into a source of knowledge and creation. Based on the photographic itinerary method, as formalised by sociologist Jean-Yves Petiteau in the course of several research projects, a framework for collaboration between researchers, photographers and respondents has been constructed, in order to document and analyse a social world, while representing it to a wider audience.